2014
DOI: 10.1002/aic.14564
|View full text |Cite
|
Sign up to set email alerts
|

A lattice Boltzmann simulation of mass transport through composite membranes

Abstract: Composite membranes with a porous support layer and a dense skin layer have been extensively used in gas separation processes. A new approach, a mesoscale Lattice Boltzmann Simulation approach, is proposed and used to model the pore‐scale gas flow and mass transfer in the inhomogeneous membrane matrixes studied. Only physical forces are considered. Chemical forces are equivalently converted to physical forces through the relaxation time. Selective permeation of moisture through a composite membrane is modeled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The equilibrium distribution functions differentiated by the macroscopic variables, from equation (12), are represented by equations (44) to (46) …”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The equilibrium distribution functions differentiated by the macroscopic variables, from equation (12), are represented by equations (44) to (46) …”
Section: Boundary Conditionsmentioning
confidence: 99%
“…As affirmed by extensive studies, [13][14][15][16][17][18][19][20] LBM has the advantages of simplicity of programming, inherent parallelism and ease in dealing with a complex boundary. The first one is the computational fluid dynamics (CFD) approach, which requires an accurate description of the pore structure and the discretization of the model into pore and solid phases, so that the microscopic equations can be solved in the pore spaces with appropriate conditions applied at the pore and solid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings of the conventional approach, lattice Boltzmann method (LBM) approach uses a mesoscopic equation to determine macroscopic transport properties. As affirmed by extensive studies, [13][14][15][16][17][18][19][20] LBM has the advantages of simplicity of programming, inherent parallelism and ease in dealing with a complex boundary. Wang et al 21 proposed a corrected heat flux of the thermal lattice Boltzmann model to calculate the effective thermal conductivity of porous media with multiphase.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation is valuable as the results can be used for estimation of membranes thickness prior to any experimental attempt, as it has been demonstrated that the initial and final membrane thickness have remarkable influence on the separation performance of fabricated membranes. [14][15][16] For example, Vogrin et al, [16] showed that the macrovoid formation can be strongly affected by the cast film thickness as they observed macrovoid formation for initial thickness of 500 μm, while for thickness lower than 300 μm, no macrovoid formation was observed. [16] It was also found that the single gas permeability increases by increasing membrane thickness, while the selectivity is independent of the membrane thickness.…”
Section: Introductionmentioning
confidence: 99%